A lignan induces lysosomal dependent degradation of FoxM1 protein to suppress β-catenin nuclear translocation - Dong, Guang-zhi (Sci Rep, 2017)
Colon cancer is one of the most common cancers. In this study, we isolated a lignan [(−)-(2R,3R)-1,4-O-diferuloylsecoisolariciresinol, DFS] from Alnus japonica (Betulaceae) and investigated its biological activity and mechanism of action on colon cancer. DFS reduced the viability of colon cancer cells and induced cell cycle arrest. DFS also suppressed β-catenin nuclear translocation and β-catenin target gene expression through a reduction in FoxM1 protein. To assess the mechanism of the action of DFS, we investigated the effect of DFS on endogenous and exogenous FoxM1 protein degradation in colon cancer cells. DFS-induced FoxM1 protein degradation was suppressed by lysosomal inhibitors, chloroquine and bafilomycin A1, but not by knock-down of proteasomal proteins. The mechanism of DFS for FoxM1 degradation is lysosomal dependent, which was not reported before. Furthermore, we found that FoxM1 degradation was partially lysosomal-dependent under normal conditions. These observations indicate that DFS from A. japonica suppresses colon cancer cell proliferation by reducing β-catenin nuclear translocation. DFS induces lysosomal-dependent FoxM1 protein degradation. This is the first report on the lysosomal degradation of FoxM1 by a small molecule. DFS may be useful in treating cancers that feature the elevated expression of FoxM1.